A critical care network pressure ulcer prevention quality improvement project. Issue 6 (30th March 2015) - McBride, Joanna; Richardson, Annette
ABSTRACT: Background: Pressure ulcer prevention is an important safety issue, often underrated and an extremely painful event harming patients. Critically ill patients are one of the highest risk groups in hospital. The impact of pressure ulcers are wide ranging, and they can result in increased critical care and the hospital length of stay, significant interference with functional recovery and rehabilitation and increase cost. Aims: This quality improvement project had four aims: (1) to establish a critical care network pressure ulcer prevention group; (2) to establish baseline pressure ulcer prevention practices; (3) to measure, compare and monitor pressure ulcers prevalence; (4) to develop network pressure ulcer prevention standards. Methods: The approach used to improve quality included strong critical care nursing leadership to develop a cross‐organisational pressure ulcer prevention group and a benchmarking exercise of current practices across a well‐established critical care Network in the North of England. The National Safety Thermometer tool was used to measure pressure ulcer prevalence in 23 critical care units, and best available evidence, local consensus and another Critical Care Networks' bundle of interventions were used to develop a local pressure ulcer prevention standards document. Results: The aims of the quality improvement project were achieved. This project was driven by successful leadership and had an agreed common goal. The National Safety Thermometer tool was an innovative approach to measure and compare pressure ulcer prevalence rates at a regional level. A limitation was the exclusion of moisture lesions. Conclusion: The project showed excellent engagement and collaborate working in the quest to prevent pressure ulcers from many critical care nurses with the North of England Critical Care Network. Relevance to clinical practice: A concise set of Network standards was developed for use in conjunction with local guidelines to enhance pressure ulcer prevention.